In Situ Atomic Force Microscopy and X‐ray Computed Tomography Characterization of All‐Solid‐State Lithium Batteries: Both Local and Overall - Chen, Weiheng; Chen, Xiaoping; Chen, Wenhua; Jiang, Zhongqing (Energy technology (Weinheim, Germany), 2023)
All‐solid‐state lithium batteries (ASSLBs) are promising due to their high‐energy output and low‐risk profile, but their development has only just begun. Atomic force microscopy (AFM) and related techniques have had an impact on ASSLBs research by elucidating the interfacial, morphological, mechanical, electrical, and electrochemical properties of a wide range of electrodes and electrolytes. However, because a cross‐section cut is necessary to define the solid–solid interface, true in situ analysis is not practical. The first part of this review will assess recent advancements in the study of ASSLBs utilizing AFM and other scanning probe microscopy techniques. The interior solid–solid interfaces can be illuminated in situ using X‐ray computed tomography (X‐CT) and other nondestructive characterization techniques, whereas, in contrast, to deepen the subject, it is further examined how X‐CT vary from the use of other instruments for solid‐state battery characterization, compare the information that various methods may give, and assess how well they can accurately reflect real batteries. This review may serve as a reference and point researchers in the direction of future study on the solid–solid interface of ASSLBs. This review examines current advances in the examination of all‐solid‐state lithium batteries using atomic force microscopy (AFM). In contrast, X‐ray computed tomography (X‐CT) and other nondestructive characterization techniques may offer considerable potential for revealing the interior solid–solid interfaces in situ. To go further into the topic, the information provided by different approaches are compared.